Effect of vagotomy on the activity of cardiac autonomic ganglia: Insight from left atrial high density frequency mapping. (1st October 2016) - Chang, Hung-Yu; Lo, Li-Wei; Chou, Yu-Hui; Lin, Wei-Lun; Lin, Yenn-Jiang; Yamada, Shinya; Chen, Shih-Ann
Abstract: Background: Both extrinsic and intrinsic cardiac autonomic nervous systems are important for initiation and maintenance of atrial fibrillation (AF). We aimed to evaluate the effect of vagotomy on the activity of cardiac autonomic ganglionated plexi (GP) and the change of dominant frequency (DF) distribution in the left atrium (LA) during AF. Methods: A mid-sternal thoracotomy was performed in 6 dogs. High frequency stimulation was applied to locate the GPs. There were four major LA GPs, which were located near the pulmonary vein ostia, and a superior vena cava-aorta (SVC-Ao) GP that was located near the superior vena cava-right atrial junction. Acetylcholine patch was applied on GPs to induce intrinsic vagal response. Vagal denervation was performed thereafter. An Ensite Array was deployed in the LA to record atrial signals before and after vagotomy during induced AF. Results: The LA mean DF values (8.2 ± 0.1 vs. 7.6 ± 0.1 Hz, p = 0.002) were higher during GP activation before than after vagotomy. The maximal DF distribution was located at the primary GPs and the nearby secondary GPs during LA GPs activation and at the LA septum and right superior pulmonary vein during SVC-Ao GP activation before vagotomy. After vagotomy, the maximal DF distribution shifted to non-GP LA sites during activation of the GPs. Conclusions: The findings suggest the important role of the extrinsic neural input in the activation and interaction of the intrinsic cardiac autonomic activity during cholinergic AF, whereas the non-GP LA sites were responsible for the AF induced without the physiological extrinsic neural input.